2020
DOI: 10.3390/rs12233939
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impacts of the COVID-19 Lockdown on Trace Gases Using Ground-Based MAX-DOAS Observations in Nanjing, China

Abstract: The spread of the COVID-19 pandemic and consequent lockdowns all over the world have had various impacts on atmospheric quality. This study aimed to investigate the impact of the lockdown on the air quality of Nanjing, China. The off-axis measurements from state-of-the-art remote-sensing Multi-Axis Differential Optical Absorption Spectroscope (MAX-DOAS) were used to observe the trace gases, i.e., Formaldehyde (HCHO), Nitrogen Dioxide (NO2), and Sulfur Dioxide (SO2), along with the in-situ time series of NO2, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
(61 reference statements)
2
12
0
Order By: Relevance
“…Due to the specific nature of events, different studies reported the effects of COVID-19 lockdowns on air quality and trace gas concentrations. Our results comply with recent studies depicting an overall decline in trace gas concentrations and an improvement in air quality [23][24][25][26][27][28][53][54][55][56][57].…”
Section: Discussionsupporting
confidence: 93%
“…Due to the specific nature of events, different studies reported the effects of COVID-19 lockdowns on air quality and trace gas concentrations. Our results comply with recent studies depicting an overall decline in trace gas concentrations and an improvement in air quality [23][24][25][26][27][28][53][54][55][56][57].…”
Section: Discussionsupporting
confidence: 93%
“…The level of O 3 in the atmosphere was not impacted by the lockdown or change in anthropogenic activity and kept on rising during the study period while the solar radiation intensified for late winter and early spring days [5,6]. O 3 measurements show notable rise in concentration during lockdown compared to pre lockdown days depicting 45% and 60% for Shanghai, 100% and 136 for Nanjing, 108% and 113% for Hefei, and 33% and 42% for Hangzhou for Level-1 and Level-2 of the COVID-19 lockdown, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is quite evident from the data that the average concentration of NO 2 over these cities dropped during end of January 2020 compared to preceding and succeeding years. Several studies have reported the decrease in tropospheric NO 2 emissions over different parts of the world during the COVID-19 lockdown [5][6][7][8][9][10][11][12]. Table 2 shows percentage change in NO2 over different cities for Level-1 and Level-2 compared to the pre-lockdown days from 2018 to 2021 where negative sign indicates reduction while positive shows increase in concentration.…”
Section: Nomentioning
confidence: 99%
See 2 more Smart Citations